Gambaran Kepuasan Pasien Rawat Jalan di RSUD Dr. T.C Hillers Maumere Kabupaten SIKKA - More, Yohana F; Littik, Serlie K. A; Sinaga, Masrida (LPPM Universitas Respati Indonesia, 2023)
Patient satisfaction is closely related to the expected service and the reality of the service that has been received. Preliminary studies show dissatisfaction related to the convenience of outpatient services at RSUD Dr. T.C Hillers Maumere, Sikka Regency. The purpose of this study was to describe the satisfaction of outpatients at RSUD Dr. T.C. Hillers Maumere, Sikka Regency. This research uses a quantitative descriptive method with a cross-sectional design. The sample size was 93 respondents taken using proportional sampling techniques. Data were analyzed using Importance Performance Analysis (IPA). The results of this study show that the reality of health services exceeds patient expectations (4.05 ≥ 3.93), with the category being very satisfied (tangibles dimension 97.7%; responsiveness dimension 97.3%; assurance dimension 99.2%; empathy dimension 98, 4%. Meanwhile, the reliability dimension (89.7%) is satisfied. The research results also show hospitals need a complaint center that is always ready to serve. Apart from that, they also need to improve orderliness in the timeliness of service, the friendliness of service, and the cleanliness of toilets. Keywords : Patient satisfaction, Tangibles, Reliability, Responsiveness, Assurance, Empathy